Portland cement paste with aligned carbon fibers exhibiting exceptionally high flexural strength (> 100 MPa). (November 2016) - Hambach, Manuel; Möller, Hendrik; Neumann, Thomas; Volkmer, Dirk
Abstract: Here, we introduce a nozzle injection technique for carbon fiber-reinforced cement paste leading to unidirectional alignment of cement-embedded short carbon fibers that follow the movement direction of the guided nozzle. In comparison to non-reinforced cement pastes, this novel material exhibits a tremendous increase of its flexural strength upon admixing and aligning 1 to 3 percent (by volume) of chopped carbon fibers. Cement pastes containing carbon fibers aligned in the stress direction thus acquire high compressive and flexural strength values at the same time. Mechanical tests prove the material to withstand flexural loads larger than 100 MPa in conjunction with a deflection hardening behavior resembling that of high performance fiber-reinforced cementious composites at relatively low fiber volume content. Insights into the preparation, fiber alignment, rheology and the fracture behavior of this material are presented in this study.